THE FEATURES OF INDUSTRIAL ENTERPRISES STRATEGIC MANAGEMENT IN THE CONDITIONS OF GLOBALIZATION (Development Service Industry Management, 2024)
In the modern global economic space, industrial companies are faced with unprecedented challenges and opportunities caused by intensive globalization processes. The transformation of the world economy, which is taking place against the backdrop of technological revolutions, digital transformation and increased international competition, requires fundamentally new approaches to the strategic management of industrial enterprises. Globalization processes significantly change traditional business models, creating a complex multidimensional system of relationships between economic entities of different countries. Industrial companies are forced to adapt to a dynamic international environment, which is characterized by high market uncertainty, constant technological changes and increased competition. In these conditions, strategic management is transformed from a planning tool into a critically important mechanism for ensuring sustainable development and competitiveness of the enterprise. The military aggression of the Russian Federation against Ukraine has caused a change in the world order, the destruction of established international relations and orders.The article is devoted to the study of the features of strategic management of enterprises in the context of globalization. It is noted that globalization processes significantly change traditional business models, creating a complex multidimensional system of interrelations between economic entities of different countries. Therefore, industrial companies are forced to adapt to a dynamic international environment characterized by high market uncertainty, constant technological change, and increased competition. The article analyzes and systematizes the positive and negative effects of globalization on the activities of industrial enterprises. Strategic development of an enterprise is a consequence of successful strategic management of the enterprise. It is emphasized that effective strategic management of an enterprise requires a systematic approach that covers all levels of the organization and provides a flexible response to global challenges and opportunities. Therefore, the article develops the process of strategic management of enterprise activities and describes in detail its stages aimed at adapting the enterprise to dynamic changes in the global environment. Particular attention was paid to the development of alternative strategies for enterprise development and it is noted that it is necessary to take into account the degree of their local sensitivity and global integration. The article shows the results of implementing the process of strategic management of enterprise activities in the context of globalization.
Keywords: development strategy; enterprise activity; globalization; foreign economic activity; strategic management of enterprise activity